Application of compression bandaging post-osteotomy results in altered pain profile; results of a single-centre randomised controlled trial. (July 2021) - Jonker, Leon; Bell, Lucy; Robinson, Kirsty; Davidson, Katherine; Dawson, Matt
Abstract: Purpose: To assess if application of dual-layer compression bandage to osteotomy patients post-surgery can positively influence levels of post-operative pain and swelling. Patients & Methods: Prospective, single-centre, randomised controlled trial comparing standard care, non-compression bandaging, versus Coban™ 2 (3M). Seven day application of the latter to index leg of osteotomy patients. Results: Primary outcome data was available for 36 out of 49 study subjects (18 standard care versus 18 Coban™ 2 subjects). Median 10-cm scale pain levels showed a statistically non-significant difference at day 5 and day 12 post-surgery between standard care and Coban™ 2 respectively: 5.5 cm vs 2.5 cm (p-value 0.068) and 4.0 cm vs 2.3 cm (p-value 0.39). However, on day 12 (p-value 0.029) and week 6 (p-value 0.027), 'throbbing pain' was significantly higher for Coban™ 2 patients. Changes in limb swelling measures, comparing before and after the surgical procedure, did not differ between treatment arms. Compression led to more patients reporting bandage-related discomfort (6% standard care versus 63% Coban™ 2 patients). Conclusion: Compression bandaging changes the post-surgery pain profile in osteotomy patients, but does not reduce leg swelling. Any subsequent leg compression trials must take into account patient comfort and titrate intervention length and compression rates.